2011
DOI: 10.1111/j.1751-2980.2011.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD4+ forkhead box P3 (FOXP3)+ regulatory T cells in inflammatory bowel disease

Abstract: METHODS: The percentage of CD4+ FOXP3 + Treg cells in PBMC was analyzed by flow cytometry. Immunohistochemistry was used to examine the FOXP3 + cells in the inflamed mucosa. Real-time polymerase chain reaction and Western blot were used to detect the expressions of FOXP3 mRNA and protein in PBMC and mucosal biopsy specimens of IBD patients, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 41 publications
(58 reference statements)
8
55
0
1
Order By: Relevance
“…Diverse data about Tregs in IBD have been reported. Wang et al (36) recently indicated that the frequency of Tregs was increased in the peripheral blood and the IBD intestinal mucosa. This phenomenon implies that Treg function is compromised in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse data about Tregs in IBD have been reported. Wang et al (36) recently indicated that the frequency of Tregs was increased in the peripheral blood and the IBD intestinal mucosa. This phenomenon implies that Treg function is compromised in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from the cultured cells as described previously [25]. The relative expression levels of TGF-β1 and Foxp3 mRNA were detected by real-time PCR (ABI7500 Fast system, UAS) using a SYBR Prime Script kit (TaKaRa, Dalian, China).…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%
“…Immunohistochemical analysis was performed using mouse anti-human TGF-β1 primary antibody (Santa Cruz, Texas, USA), mouse anti-human Foxp3 primary antibody (236A/E7, Abcam), and rabbit anti- mouse Foxp3 primary antibody (Abcam), as described previously [25]. The cut-off value for Treg expression was the median value.…”
Section: Immunohistochemistry and Double-immunofluorescence Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Exacerbated Th1 or Th17 responses have been linked to auto-immune disease [46], whereas uncontrolled Th2 responses or reduced Treg responses are associated with allergic reactions [47]. A lack of Tregs is often also found in patients with IBD [48]. Notably, several studies have reported that different strains of bifidobacteria can modulate T-cell responses in immune-driven diseases.…”
Section: T Cellsmentioning
confidence: 99%